An efficient and concise method to synthesize locked GFP chromophore analogues. Issue 47 (23rd November 2016) - Chatterjee, Soumit; Karuso, Peter
Graphical abstract: Highlights: Synthesis of a series of conformationally locked GFP fluorophores was achieved. A new faster, simpler and higher yielding synthesis of GFP fluorophores is reported. Double bond rotation is the major non-radiative pathway in these analogues. Abstract: A series of GFP analogues, which are fluorescent in the solid state at room temperature, but weakly fluorescent in solution, have been synthesized via an oxazolone formation process that involves a condensation reaction in the presence of a Lewis acid following a Knoevenagel condensation. A ring opened intermediate is formed which cyclizes readily upon heating to produce the imidazolinone. This method is faster, simpler and produces higher yields than alternative methods. A few analogues represent locked GFP derivatives where the exocyclic single bond rotation has been stopped. Weak fluorescence, even after stopping single bond rotation, indicates that restriction of conformation is not effectively controlled and that the double bond rotation is solely responsible for the major non-radiative pathway.